PENGUATAN KEJAKSAAN DALAM PENANGANAN PERKARA PIDANA MELALUI PLEA BARGANING - Iswara, I Made Agus Mahendra (Jurnal Advokasi, 2017)
Overcome crime required a crime prevention system called the criminal justice system to which it one of its subsystems, namely the prosecution conducted by the Attorney. Criminal procedure law in Indonesia has not recognized the efficiency of case handling process, so the impact on the accumulation of cases. Therefore necessary to find a solution that is one of them is the Plea Bargaining. Plea bargaining is a process of negotiation between the public prosecutor to sentence the defendant, the facts nor the article indictment with the aim to relieve the defendant. Interest Plea Bargaining is the time efficiency of case handling. Plea Bargaining has been implemented in several countries with the characteristic of each. KUHAP known that the bill "Dedicated lanes" which has characteristics similar to the Plea Bargaining.